Space Supporting Africa Volume 1: A Primary Needs Approach and Africa's Emerging Space Middle Powers - Froehlich, Annette; Siebrits, André; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In this book the background and context of Africa's political and socio-economic landscape is presented and unpacked through a primary needs approach which focuses on climate, biodiversity, health, water, education, and space-related capacity building. African theoretical contributions from the International Relations field are discussed, and Africa's new Space Policy and Strategy, along with debates around the establishment of an African Space Agency, are explored. The African International Space Ecosystem is then analyzed, including its dimensions of intra-African space relations and initiatives, African participation in COPUOS, and international space activities, agreements, and initiatives in Africa. The final part is dedicated to the national space infrastructure and activities of African states. .
Africa and the space arena -- The African international space ecosystem -- African Union member states: national space infrastructure, adtivities and capabilities.
Keywords: Africa -- Politics and government; Solar system; Africa -- Economic conditions; African Politics; Space Physics; African Economics